Securing the Healthcare Data with Blockchain Technology - A. Sonya, G. Kavitha, M. N. Karthekeyan, R. Rahul (International Journal of Advanced Science and Technology, 2020)
Cloud computing is the on-request accessibility of computer framework resources, particularly data storage (cloud storage) and accessing power, without direct dynamic active administration by the client. The term is generally used to describe servers available to numerous clients over the Internet which are put away on the far worker due its properties, for example, robustness, on-demand, pay by use, measured resources, expansive system access and ease. But the downside is data leakage, unauthorized user, insecure interface and sharing of resources that keeps clients from putting away documents on the cloud. Everyday extensive amount of data is produced in multi-pro medical clinics.This paper presents different methods to secure electronic health care reports (EHCR) in different structures like images, videos or documents etc. stored on cloud. On the off chance that specialists of different divisions need to see the human services data it will be simple for them if those are set on the cloud. This will likewise help patient ought not conveying the solutions or huge size reports.This paper tends to these issues by proposing block chain for making sure about the multiple electronic health care reports (EHCR). So as to forestall issues like penetrates and malware assaults on cloud, this inventive plan helps in significant level security to defend the documents or reports that are put away on the cloud.